2003
DOI: 10.1097/01.ju.0000091641.34674.11
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends and Characteristics of Men Choosing Watchful Waiting for Initial Treatment of Localized Prostate Cancer: Results From CaPSURE

Abstract: Purpose: Watchful waiting (WW) is one option for men with clinically localized prostate cancer. We examined temporal trends in the use of WW, as well as sociodemographic and clinical profiles of men who choose this form of management.Materials and Methods: The Cancer of the Prostate Strategic Urologic Research Endeavor is a national registry of patients with various stages of prostate cancer. Between 1989 and 2000, 5,365 men in the database were diagnosed with localized disease and elected either WW or active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(58 citation statements)
references
References 19 publications
0
56
0
2
Order By: Relevance
“…Another recent study identified predictors of eventual treatment in patients on WW, showing that PSA kinetics were a strong driver of treatment decisions. 25 Patients with a PSA increase of greater than 5 ng/ml were almost 4 times as likely to elect treatment as those with an increase of less than 2 ng/ml. High risk baseline characteristics were also significant predictors of eventual active treatment.…”
Section: National Practice Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent study identified predictors of eventual treatment in patients on WW, showing that PSA kinetics were a strong driver of treatment decisions. 25 Patients with a PSA increase of greater than 5 ng/ml were almost 4 times as likely to elect treatment as those with an increase of less than 2 ng/ml. High risk baseline characteristics were also significant predictors of eventual active treatment.…”
Section: National Practice Patternsmentioning
confidence: 99%
“…However, WW use in fact decreased from 9.5% in 1992 to 1994, to 5.5% in 1998 to 2000 with the sharpest decreases in low risk cases. 25 We subsequently looked in greater detail at treatment trends in patients at low risk and found that since the start of the PSA era, the use of WW in those at low risk has decreased by more than half from 20% in 1993 to 1995, to 8% in 1999 to 2001. During the same time the use of EBRT decreased from 13% to 7%, while that of RP decreased slightly from 55% to 52%.…”
Section: National Practice Patternsmentioning
confidence: 99%
“…Management options for patients with low or intermediate risk cancer are either a) watchful waiting (active surveillance, AS), in which the cancer is monitored without treatment until there are signs of progression, or b) radical treatment, using either prostatectomy or radiation therapy to destroy the entire prostate gland. AS has a high dropout rate, with a significant proportion of patients eventually requesting definitive therapy [2]. On the other hand, radical whole-prostate treatments carry risk of significant complications, such as impotence, incontinence and bowel dysfunction and so may represent therapeutic overkill [3].…”
Section: Introductionmentioning
confidence: 99%
“…6 The high treatment penetrance observed among patients with Gleason Grade 6 tumors suggests that although their biologic significance is unknown, these tumors possess a high level of clinical relevance for individual patients and their physicians. The magnitude of this clinical relevance is illustrated by the finding that more than 60% of all men in contemporary radical prostatectomy series in the U.S. and Europe have biopsy-detected Gleason Grade Յ 6 disease.…”
mentioning
confidence: 99%